Reversed-phase porous silica rods, an alternative approach to high-performance liquid chromatographic separation using the sequential injection chromatography technique - Satínský, Dalibor; Huclová, Jitka; Solich, Petr; Karlícek, Rolf (Journal of chromatography. A, 2003)
A commercially available porous silica rod column was used as a separation tool for the sequential injection analysis (SIA). A porous solid monolithic column showed high performance at a low pressure, allowing sequential injection analysis to be used for the first time for separation in HPLC fashion. In this contribution, we tried to demonstrate a new separation concept with SIA manifold for the simultaneous determination of four different compounds (methylparaben (MP), propylparaben (PP), triamcinolone acetonide (TCA) and internal standard ketoprofen (KP)) in a pharmaceutical triamcinolon cream 0.1% formulation. A Chromolith Flash RP-18e, 25 mm x 4.6 mm column with a 10 mm pre-column (Merck, Germany) and a FIAlab 3000 system (USA) with an 8-port selection valve and 10 ml syringe were used for sequential injection chromatographic separations in our study. The mobile phase used was acetonitrile-methanol-water (35:5:65, v/v/v) + 0.05% nonylamine, pH 2.5, flow rate 0.6 ml min(-1). The analysis time was <6 min. A novel sequential injection chromatography (SIC) technique with UV spectrophotometric detection was optimised and validated.
Keywords: Spectrophotometry, Ultraviolet; oxid křemičitý; Chromatography, High Pressure Liquid; spektrofotometrie ultrafialová; Silicon Dioxide; vysokoúčinná kapalinová chromatografie